2022
DOI: 10.3390/su14020880
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Mass Transfer at Point Electrodes Located at Cathode Support Plate in an Electrorefining Cell in Presence of Rectangular Turbulent Promoters

Abstract: Current density plays a major role in deciding the plant size, current efficiency, and energy consumption in electrorefining cells. In general, operating current density will be 40% of the limiting current density. Forced circulation of the electrolyte in the presence of promoters improves the mass transfer coefficient. In the present study, rectangular turbulence promoters are fitted at the bottom side of the cell to improve the mass transfer coefficient at the cathode support plate. The limiting current dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In the study of Brar [14], he statistically evaluates the random geometric imperfection stability for an asymmetrical cylindrical vessel under external pressure, while the relevant EN standard controls the relevant safety at the limit of the stability capacity with respect to geometric imperfections. In [15], the authors focus on electrolyte and recirculation tanks considering the technology itself but not the stability, confirming the need for safe rigidly stable tanks, although this is outside of the scope of our study.…”
Section: Introductionmentioning
confidence: 58%
“…In the study of Brar [14], he statistically evaluates the random geometric imperfection stability for an asymmetrical cylindrical vessel under external pressure, while the relevant EN standard controls the relevant safety at the limit of the stability capacity with respect to geometric imperfections. In [15], the authors focus on electrolyte and recirculation tanks considering the technology itself but not the stability, confirming the need for safe rigidly stable tanks, although this is outside of the scope of our study.…”
Section: Introductionmentioning
confidence: 58%
“…Generally, high-speed flowing of the electrolyte is regarded as an important way to eliminate machining products in time and improve machining performance. However, many studies have also shown that blindly increasing the electrolyte velocity cannot have a significant impact on the machining performance because ECM is a complex multi-physics coupling process [37,38]. This study proposes an interesting approach to improve machining performance through energy conversion of electrolyte fluid during ECM processes, as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…This process is categorized into electrodeposition/electrowinning or electrorefining. The recovery of precious metals via electrowinning involves the use of direct current between the anode and cathode electrodes so aid the reduction of the targeted metals specie in the effluent of the cathode and to extract the metal in its metallic form (Subbaiah et al 2022). However, in electrorefining, the anode consisting the metals associated with impurities is dissolved in an aqueous state by either direct or indirect electrooxidation, leading to the selective deposition of leached metal ions unto the cathode in its pure form (Rai et al 2021;Subbaiah et al 2022).…”
Section: Electrochemical Technologymentioning
confidence: 99%
“…The recovery of precious metals via electrowinning involves the use of direct current between the anode and cathode electrodes so aid the reduction of the targeted metals specie in the effluent of the cathode and to extract the metal in its metallic form (Subbaiah et al 2022). However, in electrorefining, the anode consisting the metals associated with impurities is dissolved in an aqueous state by either direct or indirect electrooxidation, leading to the selective deposition of leached metal ions unto the cathode in its pure form (Rai et al 2021;Subbaiah et al 2022). This precious metal recovery approach has notable significant merits such as uniform selective and uniform deposition of metals, high purity grade, automation, faster reaction kinetics, and cost-effectiveness.…”
Section: Electrochemical Technologymentioning
confidence: 99%